Gender diversity on superannuation trustee boards in Australia – evidence from profit-to-member funds. (3rd July 2022) - Westcott, Mark; Nguyen, Tien
ABSTRACT: There has been a sustained public policy focus on the governance of superannuation funds in Australia due to the compulsory nature of the superannuation system established in 1992. Much of the attention on governance relates to the independence of directors on the trustee board companies of profit-to-member funds. Little consideration has been given to the gender diversity of these boards. This article explores changes to gender diversity on the trustee boards of 59 profit-to-member superannuation funds between 2010 and 2019. It shows a steady increase in the proportion of females appointed to these boards over this ten-year period. It draws out some important differences in female representation on public offer and non-public offer superannuation funds. It also reveals differences in the rate and extent of female representation among member and employer representatives on these trustee boards. Finally, it shows that there is a widening pool of females appointed to superannuation trustee boards rather than a shallow pool of women who serve on multiple boards.